Multiplicities of Peano maps: on a less known theorem by Hurewicz - Dębski, Wojciech; Mioduszewski, Jerzy (Annales Mathematicae Silesianae, 1995)
It is shown that the values of two highest multiplicities of Peano maps cannot be the values of openess. This adds a new detail to the results by Hurewicz (1933), concerning dimension raising maps, when they are restricted to maps from the closed interval into the plane.